Social Indicators for Integrating the Circular Economy into Infrastructure Projects in Malaysia - Rafiee Razak; Yong Siang Lee; Ahmad Rizal Alias; Rahimi A. Rahman (Journal of Engineering, Project, and Production Management)
The adoption of the circular economy (CE) in infrastructure projects has grown in recent years, significantly contributing to sustainable development. However, the integration of the CE into Malaysia’s infrastructure projects has social aspects that remain underexplored. This study aimed to, first, identify key social indicators that define the integration of CE principles into infrastructure development and, second, propose strategies to enhance the inclusion of these social dimensions. Thematic analysis was conducted on data collected through in-depth interviews with 18 respondents from diverse sectors of the infrastructure industry, including clients, consultants, contractors, and suppliers. Three main social indicators were identified: engagement, quality of life, and attractiveness. Strategies such as integration, regulatory policy, and transparency were found to be crucial for advancing the inclusion of social aspects in CE practices. The findings offer insights on integrating social factors into CE frameworks, promoting more inclusive and sustainable infrastructure development.